A review of the epidemiology and control of brucellosis in Malaysia - Bahaman, Abdul Rani; Joseph, P. G.; Bejo, Siti Khairani (Veterinary Association Malaysia, 2007)
The presence of brucellosis in large ruminants and pigs in Malaysia was confirmed by the isolation of Brucella abortus in 1950 and Brucella suis in 1963, respectively. Subsequently, brucellosis was detected in humans (1980), dogs (1982) and sheep(1991). The National Programme for 'The Area-wise Eradiction of Bovine Brucellosis 'which came into effect in 1979 had reduced the prevalence of bovine brucellosis in Malaysia from 3.3% in 1979 to 0.23% in 1988. It was then envisaged that by 1995 bovine brucellosis in Malaysia had been eradicted. However, the prevalance of brucellosis in cattle was reported to be high (<2%) again (Anon,2005). In the state of Pahang, there was a surge in prevalence from 0.2% in 1996 to 13% in 1998 but was brought down to 1.8% in 2005 by stringent testing, culling and vaccination. The success of the eradiction programme in the later phase proved to be difficult due to the remote geographical distribution of the animals, the extensive farming system being practised and the education and social status of the farmers. In the later phase of the programme, it was difficult to detect infected animals in the herds as the prevalence of infection was very low. It therefore, became necessary to test every animal so as not to miss the few inapparent carrier animals. For this, the enzymelinked immunosorbent assay was a useful test and was included, in addition to the Rose Bengal plate test (RPBT), to complement fixation test (CFT) and the Milk Ring Test (MRT)in the screening and diagnosis of brucellosis. Bacterial culture and isolation of suspected cases of bovine brucellosis (abortion, retained placenta) were additional measures undertaken to detect animals.